Arduino-Based RFID Door Lock Security System with Piezo Electric Sensor and GSM Module for Venezia Townhomes in Sta. Maria, Bulacan: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Arduino-based RFID Door Lock Security System with Piezoelectric Sensor and GSM Module for Venezia Town Homes in Santa Maria, Bulacan, is a digital security lock that will help minimize the crime rate index and reduce homeowners' worries. The researchers used a quantitative survey method with a purposive sampling technique, T-test, and Likert Scale. The information acquired came from the survey questionnaire, which was used to confirm the project's accuracy. The study utilized selected thirty-two (32) homeowners and three (3) security personnel of Venezia Townhomes. Thirty-five (35) respondents were chosen for the study.
Keywords: Arduino; RFID; Door Lock; GSM Module; Piezoelectric; Sensor; Security